The mental health of Chinese elite athletes: revisiting the assessment methods and introducing a management framework - Si, G.; Li, X.; Huang, Z.; Wang, D.; Wang, Y.; Liu, J.-D.; Liu, H.; Zhao, D.; Bu, D.; Zhang, C.-Q. (International Journal of Sport and Exercise Psychology, 2025)
In this paper, we described our recent thinking on the mental health assessment methods of Chinese elite athletes and introduced a contextually appropriate sport training centre-based mental health management framework for Chinese elite athletes. Regarding the assessment methods, we highlighted the two-dimensional measures of mental health including both the negative dimension of psychopathology and the positive dimension of wellbeing. Then, we introduced our recently developed mental health management framework for Chinese elite athletes that consists of three main parts: (a) annual mental health screening, (b) follow-up and mental health emergency intervention, and (c) mental health literacy education. We provided three examples demonstrating how this management framework can be applied. We call for future research applying this management framework and scale up the mental health screening by adopting the two-dimensional measures of mental health, prevention, and intervention nationwide.